Penyisihan Konsentrasi Chemical Oxygen Demand (COD) Pada Buangan Akhir Pengolahan POME - Ikhwanul Ikhsan; David Andrio; Jecky Asmura (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Problem of Palm Oil Mill Industry is concentration of chemical oxygen demand POME final discharge failed to comply discharge standard. In this research, we propose a treatment for POME final discharge using adsorption and coagulation to reduce chemical oxygen demand (COD). Our result showed based on adsorption process with a ratio of 10 g/l powdered activated carbon reduce 88% COD and coagulation using poly aluminium chloride (PAC) reduce 88% COD.Keywords: POME final discharge, powdered activated carbon, poly aluminium chloride